(untitled) (Research, Society and Development, 2020)
Deforestation has followed population’s growth and development for thousands of years. Climate, culture, technology and commerce have influence on the acceleration or deceleration of the pace of deforestation. It is estimated that approximately 50% of the Cerrado (savanna) biome area has already been cleared to make way for agricultural fields, pasturelands and urban areas. Aiming to disseminate the current simplified deforestation detection procedures, generally performed manually by photointerpretation of satellite images, this study presents, tests and validates the hypothesis that it is possible to perform the monitoring by mathematical operations between thematic maps of remnant vegetation. A case study performed in a 3,865Km2 area, where the variation of vegetation cover was studied using satellite imagery Landsat 5 TM and Geographic Information Systems (GIS), showed that it is possible to carry out the proposed procedure with accurate results and in less time than the one needed for photointerpretation technique. The objective of this research was to quantitatively evaluate the area covered with vegetation in the municipality of São Gabriel do Oeste, for the years 1999 and 2009, through the elaboration of Remaining Vegetation Maps, a product of remote sensing techniques in the PCI Geomatica Focus software.